A Novel and Secure Pseudovirus Reporter System Based Assay for Neutralizing and Enhancing Antibody Assay Against Marburg Virus - Bi, Jinhao; Wang, Haojie; Pei, Hongyan; Han, Qiuxue; Feng, Na; Wang, Qi; Wang, Xinyue; Wang, Zhenshan; Wei, Shimeng; Ge, Liangpeng; Wu, Meng; Liang, Hao; et al. (Frontiers in Microbiology, 2022)
Marburg virus (MARV) is one of the principal members of the filovirus family, which can cause fatal hemorrhagic fever in humans. There are currently no prophylactic and therapeutic drugs on the market, and the high pathogenicity and infectivity of MARV make its research highly dependent on biosafety level 4 conditions, severely hindering the development of vaccines and therapies. Therefore, the development of medicines such as MARV serological diagnosis, vaccines, and therapeutic antibody drugs urgently need a safe, convenient, and biosafety level 2 detection method to measure the neutralizing activity of MARV antibodies. To this end, we report a neutralization assay relying on a Rabies virus (RABV) reverse genetic operating system. We constructed infectious clones carrying the eGFP reporter gene and the full length of the original unmodified MARV GP gene. Based on the critical parameters of phylogenetic analysis, recombinant viruses targeting representative strains in the two major MARV lineages were successfully rescued. These pseudoviruses are safe in mice, and their inability to infect cells after being neutralized by antibodies can be visualized under a fluorescence microscope. We tested the system using the neutralizing antibody MR191. MR191 can significantly block the infection of BSR cells with pseudovirus. We compared it with the traditional lentivirus-type pseudovirus system to verify the system's credibility and obtained the same results as reported in the literature. In general, we have established a safe and visualized method for evaluating the neutralizing activity of MARV antibodies. Compared with traditional methods, it has the advantages of convenient operation, short cycle, and low cost. It is a candidate method that can replace actual viruses for a neutralization assay.